Formal approach based on petri nets using agent paradigm for m-maintenance, ISSN / e-ISSN 1757-8787 / 1757-8779 - Abid Khadija; Mouss Leila Hayet; Kazar Okba; Kahloul Laid (International Journal of Critical Computer-Based Systems, 2017)
The long use of a system in a manufacturing environment causes its degradation, thus the maintenance activity is required in this environment to keep and to improve the efficiency of the system. The new development in networking technologies enhances maintenance strategies and gives birth to remote maintenance (tele-maintenance, e-maintenance, m-maintenance). This maintenance makes information available anywhere/anytime and provides maintenance-personnel with the necessary information at the suitable time. This new type of maintenance reduces the maintenance costs and solves the problem of the unavailability of experts. Mobile agent as a rich design concept brings many facilities in the development of m-maintenance, however few works are elaborated in this stage. The objective of this work is both: 1) the proposition of a based mobile multi-agent architecture dedicated for m-maintenance in manufacturing systems; 2) the exploitation of high level petri nets in the specification, simulation and verification phases of the architecture development.